Deciphering Customer Perceptions of Academic Library Features - Ball, Kathy (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
This paper describes a qualitative analysis of comments made by respondents of a LibQUAL+ survey administered at McMaster University Library by a research team comprising a librarian and a faculty member. The qualitative analysis sheds light on quantitative findings from the survey about customer perceptions of academic library features. Cet article décrit l’analyse qualitative de commentaires formulés par les répondants d'un sondage LibQUAL + administré à la Bibliothèque de l'Université McMaster par une équipe de recherche comprenant un bibliothécaire et un membre du corps professoral. L'analyse qualitative éclaire les résultats quantitatifs de l'enquête sur la perception par les utilisateurs des particularités des bibliothèques universitaires.